2020
DOI: 10.1002/lrh2.10235
|View full text |Cite
|
Sign up to set email alerts
|

Transmission dynamics: Data sharing in the COVID‐19 era

Abstract: ProblemThe current coronavirus disease 2019 (COVID‐19) pandemic underscores the need for building and sustaining public health data infrastructure to support a rapid local, regional, national, and international response. Despite a historical context of public health crises, data sharing agreements and transactional standards do not uniformly exist between institutions which hamper a foundational infrastructure to meet data sharing and integration needs for the advancement of public health.ApproachThere is a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…Examples of this work include: ( Stoll et al, 2020 ; Smith et al, 2020 ) Improve open data and data sharing platforms to facilitate the exchange of information about the societal impacts of COVID-19, to enable more rapid and coordinated responses to future shocks. Other fields are also calling for data sharing to respond to COVID-19 ( Moorthy et al, 2020 ; Oliver et al, 2020 ; Foraker et al, 2020 ) Longer-term research needs: To design future response strategies in support of the ‘tropical majority’ of small-scale fish producers and traders, draw on lessons from social safety net programs in other food sectors, and experience with implementing the Human Right to Food Improve information systems to track fish prices and trade volumes typically consumed by different types of consumers (particularly in LMICs) to reduce wasted fish and enable value chains to respond to consumers' nutrition needs and demand preferences. This may include full traceability of species and stocks based on molecular/DNA analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of this work include: ( Stoll et al, 2020 ; Smith et al, 2020 ) Improve open data and data sharing platforms to facilitate the exchange of information about the societal impacts of COVID-19, to enable more rapid and coordinated responses to future shocks. Other fields are also calling for data sharing to respond to COVID-19 ( Moorthy et al, 2020 ; Oliver et al, 2020 ; Foraker et al, 2020 ) Longer-term research needs: To design future response strategies in support of the ‘tropical majority’ of small-scale fish producers and traders, draw on lessons from social safety net programs in other food sectors, and experience with implementing the Human Right to Food Improve information systems to track fish prices and trade volumes typically consumed by different types of consumers (particularly in LMICs) to reduce wasted fish and enable value chains to respond to consumers' nutrition needs and demand preferences. This may include full traceability of species and stocks based on molecular/DNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Improve open data and data sharing platforms to facilitate the exchange of information about the societal impacts of COVID-19, to enable more rapid and coordinated responses to future shocks. Other fields are also calling for data sharing to respond to COVID-19 ( Moorthy et al, 2020 ; Oliver et al, 2020 ; Foraker et al, 2020 )…”
Section: Discussionmentioning
confidence: 99%
“…The vision pursued in these initiatives is still under active development, and has required a vast community of clinicians, researchers, informaticians, developers, industry and government representatives, and beyond coming together with the common objective of addressing the technical, policy or legal, and cultural hurdles to enable more effective management of the COVID-19 pandemic. It has been argued that infrastructure is currently sorely lacking in most public health organisations to realise this vision effectively or efficiently [ 81 ]. There are still many unanswered questions about how to overcome bias and determine causality through real-world data [ 24 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 , 4 Simultaneously, there was a high demand for rapid and ongoing scientific information related to COVID‐19 to support leaders' decision‐making. 5 , 6 Previous experience from outbreaks has demonstrated that reliable and timely scientific information is vital for informed decision‐making. 7 , 8 For instance, lessons learned from the Ebola disease outbreak confirmed that lack of real‐time information can considerably affect the decisions of frontline responders which placed public health and healthcare providers at serious risk.…”
Section: Introductionmentioning
confidence: 99%